The role of mental revolution training on the improvement of civil servant professionalism in public services in DKI Jakarta Provincial Government - Budi Sukmajadi (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2019)
The responsibility of State Civil Servant (ASN) has been clearly stated in the ASN Law. Furthermore, it is also regulated in Government Regulations concerning Employee Discipline. Nonetheless, there is still negative stigma in the implementation and the community judgement, such as laziness in work, money orientation in completing administrative service tasks, misunderstanding of the main duties and functions of the employees, breaking the regulation and looking for shortcuts to achieve goals in gaining positions and even worse, performing corruption. This paper discusses the idea of the role of mental revolution training to become more productive and professional ASN. The mental revolution training is a concrete step in shaping the mental of professional public servants. The subjects of public service mental revolution training material refers to how an ASN should have perspective, way of thinking and working thus that it is likely expected that the training could improve the professionalism of ASN as public servants.